Membangun Ketahanan Keluarga pada Masyarakat Pekerja Bangunan Perspektif Hukum Keluarga Islam - Wendi Prasetiyo; Zuraidah (Journal of Sharia and Legal Science, 2024)
The study discusses building family resilience in the community who work as construction workers. This is because generally working as a construction worker is considered a trivial job by the community because of its status and income which are considered low in this case uncertain, so that they often have difficulty in meeting their family's needs even for daily living expenses and children's school fees. Conditions like this cause disputes between family members and often lead to strained relationships which no longer create a harmonious atmosphere due to economic pressures resulting from income being less than the needs that must be met. This study aims to understand efforts to build family resilience in the construction worker community in Pasar Baru Pangkalan Balai, Banyuasin Regency and a review of Islamic family law on these efforts. This type of research is field research using empirical legal methods. The results of the study show that several efforts by construction workers in Pasar Baru Pangkalan Balai, Banyuasin Regency to build family resilience include working as construction workers, looking for side jobs, establishing good communication and saving expenses. A review of Islamic family law on how to build family resilience is by prioritizing the creation of household welfare, especially the relationship between husband and wife. There are several tips used to build family resilience, namely by managing emotions, strengthening relationships, straightening intentions, and not forgetting to always be grateful.